THE CORRELATION OF READING HABIT TO READING COMPREHENSION IN AN EFL CONTEXT AT UNIDAYAN BAUBAU - Suharja Suharja (English Education Department, 2019)
The main objective of this research is to find out to what extent the correlation between reading habit and reading comprehension of the students of Unidayan Baubau. This research is ex post facto with quantitative approach. The instruments of the research are questionnaire and reading comprehension test. They are administered to 197 students of Unidayan Baubau. The result of the research indicated that the students’ reading habit in Unidayan Baubau is in moderate level. This conclusion obtains from descriptive data which reveals that mean score of students’ reading habit is 129.79 and 89 students or 45.2 % of all participants has moderate reading habit with range score from 123.91 to 135.68. The researcher found that the students’ reading comprehension in Unidayan Baubau is in moderate level as well. This conclusion obtains from descriptive data which reveals that mean score of students’ reading comprehension is 54.53 and 95 students or 48.2 % of all participants has moderate reading comprehension with range score from 48.97 to 60.09. The researcher found that there is significant correlation between reading habit and reading comprehension. It can be seen that students’ reading habit and reading comprehension denote a positive correlation. It can be seen from r coefficient is 0.748. The researcher also found that there is significant correlation between reading habit toward reading comprehension. It can be seen from the analysis result which reveals that Fobserved is 248.06 with probability value or p is 0.000 and determinant coefficient (R Square) is 0.560. It means that reading habit influenced 56 % of students’ reading comprehension while 44 % influenced by other variables.